A methodology for measuring product innovation: A case study for a manufacturing system - (:unkn) unknown (Inderscience Publishers, 2011)
In this study, a general definition of the product innovation for the manufacturing suit as well as vital importance of measuring techniques for that is elaborated. Although there are various studies aimed to measure the product innovation, there is not a consensus on a generic model that can be applied to every manufacturing system. Therefore, the main motivation of this study is to fulfil this gap by defining a methodology to measure the product innovation based on four quantifiable indicators which can easily be adopted for different manufacturing bodies. These indicators mainly depend on the changes in the product portfolio and listed as: 'change in product portfolio', 'new product ratio', 'sales amount ratio of new products', and 'sales revenue ratio of new products'. Calculation methods of these indicators are clearly identified. Depending on the results of these indicators the degree of product innovation is formulated using the weighted change in each of these elements. In order to verify and validate the method, it is employed to measure the product innovation of a manufacturing suit. According to the results of the case study, it can be deduced that the proposed model well meets the requirements of innovation measurement. Copyright © 2011 Inderscience Enterprises Ltd.
Keywords: Change management; Manufacturing technology; Measuring product innovation; Product portfolio